2022
DOI: 10.3389/fcimb.2022.893044
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP and Imbalance of CD4+ T Cell Compartment in Pediatric COVID-19

Abstract: Severe COVID-19 in children is rare, but the reasons underlying are unclear. Profound alterations in T cell responses have been well characterized in the course of adult severe COVID-19, but little is known about the T cell function in children with COVID-19. Here, we made three major observations in a cohort of symptomatic children with acute COVID-19: 1) a reduced frequency of circulating FoxP3+ regulatory T cells, 2) the prevalence of a TH17 polarizing microenvironment characterized by high plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Severe COVID-19 in children is rare. Compared with healthy controls, children with acute COVID-19 infections, whether severe or mild, all exhibited higher plasma levels of ATP that were negatively correlated with the frequency of regulatory T cells but positively correlated with the frequency of CD4+ T cells [ 284 ]. Conversely, the level of CD4+ T cells—regarded as a biomarker of protective immunity [ 285 ]—is usually significantly reduced in adults with severe or critical COVID-19 compared to healthy controls [ 286 ].…”
Section: Melatonin Is An Ancient Molecule That Can Regulate Virus Pha...mentioning
confidence: 99%
“…Severe COVID-19 in children is rare. Compared with healthy controls, children with acute COVID-19 infections, whether severe or mild, all exhibited higher plasma levels of ATP that were negatively correlated with the frequency of regulatory T cells but positively correlated with the frequency of CD4+ T cells [ 284 ]. Conversely, the level of CD4+ T cells—regarded as a biomarker of protective immunity [ 285 ]—is usually significantly reduced in adults with severe or critical COVID-19 compared to healthy controls [ 286 ].…”
Section: Melatonin Is An Ancient Molecule That Can Regulate Virus Pha...mentioning
confidence: 99%
“…Of course, should this mechanism be operative in vivo, the obvious implication is that sufficient amounts of eATP should be present in the blood. Anecdotal reports suggest that this might be the case in COVID-19 [77,78].…”
Section: P2x7r and Covid-19mentioning
confidence: 97%
“…The DAMP most frequently reported for COVID-19 is lactate dehydrogenase, a central enzyme of anaerobic glycolysis that is present in virtually all cells and that, therefore, reliably indicates cell death when occurring at high concentrations in the extracellular space ( 200 202 ). Other DAMPs which have been observed at elevated levels in the blood or plasma of patients with severe COVID-19 comprise high-mobility group box protein (HMGB)1 ( 51 , 110 , 111 , 202 206 ), S100 proteins ( 108 , 110 , 202 , 207 209 ), plasma hyaluronan ( 210 ), extracellular (e)ATP ( 211 , 212 ), the antimicrobial peptide LL-37 ( 213 , 214 ), histones (e.g ( 215 217 ), reviewed in ( 218 , 219 ) and circulating self-DNA, including nDNA ( 13 , 20 , 21 , 42 , 46 , 47 ), mtDNA ( 13 , 18 , 21 , 42 , 43 , 48 , 49 ), NET-associated cfDNA ( 201 , 215 , 220 222 ), histone-DNA complexes ( 219 ), and cfDNA of non-specified subcellular origin ( 45 , 48 , 50 54 ). As recently reviewed for sepsis ( 72 ), most of these studies reported a positive correlation of the plasma levels of at least some of the beforementioned DAMPs with the degree of disease severity (e.g., mild versus severe cases, COVID-19 patients at ICU admission versus healthy controls, ICU-admitted cases with fatal outcomes versus surviving patients, poor oxygenation status, patients with acute respiratory distress syndrome or with multisystem inflammatory syndrome in children, etc.).…”
Section: Damps and Inflammasomes – A Smart But Dangerous Liaisonmentioning
confidence: 99%